2002
DOI: 10.1046/j.1471-4159.2002.00967.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of nuclear Ca2+/calmodulin‐dependent protein kinase II and brain‐derived neurotrophic factor gene expression by stimulation of dopamine D2 receptor in transfected NG108‐15 cells

Abstract: We identified the isoforms of Ca 2+ /calmodulin-dependent protein kinase II (CaM kinase II) subunits in rat striatum. All four subunits of CaM kinase II a, b, c and d were detected including the isoforms of aB, cA, cA¢, cA.B, d3 and d7 with nuclear localization signal. We established NG108-15 cells with the stably expressed dopamine D2L receptor (D2LR, long form), which is an alternative splicing variant. The cells were termed NGD2L. Immunostaining demonstrated that D2LR was localized in plasma membranes. Calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 53 publications
7
64
1
Order By: Relevance
“…Ethanol sensitizes D 2 autoinhibition S Perra et al (Hernandez-Lopez et al, 2000;Hu et al, 2005;Takeuchi et al, 2002;Vallar et al, 1990). Thus, we examined the effects of pharmacological treatments that interfere with this signaling pathway on outward currents produced by 10-min perfusion of quinpirole (300 nM) ( Figure 5).…”
Section: Regulation Of D 2 Receptor-mediated Inhibition By a Ca 2 + -mentioning
confidence: 99%
See 1 more Smart Citation
“…Ethanol sensitizes D 2 autoinhibition S Perra et al (Hernandez-Lopez et al, 2000;Hu et al, 2005;Takeuchi et al, 2002;Vallar et al, 1990). Thus, we examined the effects of pharmacological treatments that interfere with this signaling pathway on outward currents produced by 10-min perfusion of quinpirole (300 nM) ( Figure 5).…”
Section: Regulation Of D 2 Receptor-mediated Inhibition By a Ca 2 + -mentioning
confidence: 99%
“…All of these treatments produced B50% increases in the average peak amplitude of quinpirole-induced currents compared with the value obtained under control conditions (Figure 5c). D 2 receptor-induced Ca 2 + rises may lead to activation of CaMKII (Takeuchi et al, 2002) or protein kinase C (PKC) (Gordon et al, 2001). The CaMKII inhibitor KN-62 (10 mM, 41-h preincubation plus intracellular dialysis) and CaMKII inhibitory peptide (fragment 290-309; 25 mM, intracellular dialysis) significantly reduced the amount of quinpiroleinduced desensitization, whereas PKC inhibitory peptide (fragment 19-31; 25 mM, intracellular dialysis) had no significant effect (Figures 5a and b).…”
Section: Regulation Of D 2 Receptor-mediated Inhibition By a Ca 2 + -mentioning
confidence: 99%
“…It has been reported that stimulation of dopamine D1 receptor increases intracellular Ca 2+ concentration via activation of phospholipase C-inositol-1,4,5-trisphosphate signaling pathway (Pacheco and Jope, 1997;Jin et al, 2003). Dopamine-induced Ca 2+ responses are also modulated by dopamine D2 receptor (Zhu et al, 1997;Takeuchi et al, 2002). On the other hand, dopamine D3 receptor usually coexists with dopamine D 1 and D 2 receptors (Surmeier et al, 1992;Schwartz et al, 1998) and contributes to the inhibitory effects of dopamine D1 and/or D2 receptor-mediated signaling (Mizuo et al, 2004b).…”
Section: Activation Of Astrocytes By Bpamentioning
confidence: 99%
“…D2R mRNA levels in NB2A cells were comparable to those seen in cerebral cortex (data not shown). Next, we evaluated basal activities of the D2R promoter by luciferase assays in NB2A cells and two other cell lines that do not express D2R, NG108-15 (Takeuchi et al 2002) and C6 glioma cells (Valdenaire et al 1994) (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
“…PCR products were separated by electrophoresis on 1.0% agarose gels and visualized by ethidium bromide staining. As positive controls PCR products derived from D2LR and D2SR expression vector templates (Takeuchi et al 2002) were electrophoresed at the same time.…”
Section: Rt-pcrmentioning
confidence: 99%